Rethinking 'Peace' in International Law and Politics From a Queer Feminist Perspective. Issue 1 (November 2020) - Otto, Dianne
What does peace mean in today's world of endless wars? Why has the project of 'universal peace', so ardently hoped for by the drafters of the UN Charter in 1945, failed so profoundly? I reflect on these questions through three stories of peace. The first is told by a series of four stained-glass windows in the Peace Palace in The Hague; the second is of the world's demilitarised zones; and the third of a peace community in Colombia. These stories provide a springboard to reflect on how we might rethink peace in the context of today's world, drawing on feminist, queer and postcolonial analyses. My discussion exposes the limits of the UN Charter's approach to peace, and the impossibility of its methods ever achieving 'universal peace'. The Charter's reliance on militarism and collective enforcement, as well as its commitment to peace as an evolutionary process, maintain rather than dismantle global hierarchies of domination. I also question the dualism of war and peace, which obscures much of the violence of what we call peace. The task of rethinking peace is urgent. To do so we need to go beyond the worlds we know, beyond the confines of law and the inevitability of quotidian hierarchies of gender, sexuality and race, to invent new methods of peace-making, outside the 'frames of war'.